Development of magneto immunosensors for the detection of dengue NS1 protein - Bundalian, Reynaldo DL Jr. (2013)
Dengue is considered as one of the most important vector-borne disease affecting several regions. As a disease of public health importance, timely diagnosis during dengue infection remains relevant to clinical management and disease surveillance. While several forms of diagnostic tests for dengue are available, many of these tests are not employed for routine testing due to the inherent cost and requirement for specialized laboratories. This, therefore, emphasizes the need for alternative dengue diagnostic tests which can be more accessible for routine applications. The objective of this study was to develop alternative immunosensing strategies for the dengue NS1 antigen in the form of an optical immunosensor and electrochemical immunosensor that employs immunomagnetic separation strategy. The surface of tosyl-activated magnetic beads were initially functionalized and modified with dengue group specific polyclonal anti-dengue NS1 antibodies and used as capture ligand for the indirect sandwich immunoassay approach used in the optical immunosensor and electrochemical immunosensor. The optimal immunoreagent concentration for both immunosensors were first studied and optimized. Following the optimization, important analytical parameters were analyzed and defined for the immunosensors. The LOD of the optical immunosensor and electrochemical immunosensor were 15.77 ng ml-1 and 8.63 ng ml-1 respectively with the electrochemical immunosensor being more sensitive than the optical immunosensor. These LOD values are both within clinically relevant levels of the dengue NS1 antigen during the early course of infection emphasizing the potential clinical usefulness of the two systems. The optical and electrochemical immunosensor also have linear range value of 7.81 ng ml-1 to 500 ng ml-1 and LOQ values of 52.57 ng ml-1 and 49.73 ng ml-1 respectively. The LOQ established for both detection systems allows possible quantification of the dengue NS1 antigen at concentrations previously associated with DHF progression.
Permission: Available to the general public
Thesis (DrPH Medical Microbiology)--University of the Philippines Manila, 2013
Keywords: Dengue